2017
DOI: 10.1016/j.jempfin.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Systematic cojumps, market component portfolios and scheduled macroeconomic announcements

Abstract: This study provides evidence of common bivariate jumps (i.e., systematic cojumps) between the market index and style-sorted portfolios. Systematic cojumps are prevalent in book-tomarket portfolios and hence, their risk cannot easily be diversified away by investing in growth or value stocks. Nonetheless, large-cap firms have less exposure to systematic cojumps than small-cap firms. Probit regression reveals that systematic cojump occurrences are significantly associated with worse-than-expected scheduled macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Several studies (see, for instance, Fair, 2003;Birz and Lott, 2011) found that, due to the leading role of the US in the world economy, the release of US macroeconomic announcements attract the interest of stock markets worldwide and produce significant effects on those financial markets more integrated with the US economy. Among all variables, the Fed rate is one of the most closely watched by equity market participants (Bernanke and Kuttner, 2005;Chan et al 2008), together with the rate of US inflation (Moerman and Van Dijk, 2010), US labour market dynamics, GDP, unemployment, retail sales and durable goods (Birz and Lott, 2011), and finally the US nonfarm payroll, which is indicated to be the 'king of all news' (Andersen and Bollerslev, 1998;Wongswan, 2006). Finally, the forward-looking Institute for Supply Management (ISM) index is important because, by monitoring employment, production, new orders, and inventories, it describes the US economy's perceived state.…”
Section: Spillovers: Time-varying Volatility and The News Approachmentioning
confidence: 99%
“…Several studies (see, for instance, Fair, 2003;Birz and Lott, 2011) found that, due to the leading role of the US in the world economy, the release of US macroeconomic announcements attract the interest of stock markets worldwide and produce significant effects on those financial markets more integrated with the US economy. Among all variables, the Fed rate is one of the most closely watched by equity market participants (Bernanke and Kuttner, 2005;Chan et al 2008), together with the rate of US inflation (Moerman and Van Dijk, 2010), US labour market dynamics, GDP, unemployment, retail sales and durable goods (Birz and Lott, 2011), and finally the US nonfarm payroll, which is indicated to be the 'king of all news' (Andersen and Bollerslev, 1998;Wongswan, 2006). Finally, the forward-looking Institute for Supply Management (ISM) index is important because, by monitoring employment, production, new orders, and inventories, it describes the US economy's perceived state.…”
Section: Spillovers: Time-varying Volatility and The News Approachmentioning
confidence: 99%
“…Pelger (2020), Bollerslev et al (2008) and Bollerslev et al (2013) provide strong evidence of systematic cojump risk embedded in the cross-section of high-frequency returns. Other related works include jump dependence tests (Bollerslev et al, 2013), cross-sectional assessments (Bibinger et al, 2019;Chan et al, 2017), and risk diversification analyses (Gilder et al, 2014;Bollerslev et al, 2008;Todorov and Bollerslev, 2010), among others. 1 In this paper, we argue that bifurcating jumps into idiosyncratic or systematic classes is too restrictive to adequately characterize systemic (market-wide) risk.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of these studies has investigated cojumps between the agricultural futures market and the stock market, nor explored cojumps' abilities to predict stock market volatility. Moreover, the existing literature (e.g., Chan, Bowman, & Neely, 2017;Chatrath, Miao, Ramchander, & Villupuram, 2014;Clements & Liao, 2017;Lahaye et al, 2011;Piccotti, 2018) has found that cojump occurrences are always related to macroeconomic news. Moreover, the existing literature (e.g., Chan, Bowman, & Neely, 2017;Chatrath, Miao, Ramchander, & Villupuram, 2014;Clements & Liao, 2017;Lahaye et al, 2011;Piccotti, 2018) has found that cojump occurrences are always related to macroeconomic news.…”
Section: Introductionmentioning
confidence: 99%
“…Groß-Klußmann and Hautsch (2011), Lahaye, Laurent, and Neely (2011), and Maslyuk-Escobedo, Rotaru, and Dokumentov (2017 empirically find that trading on financial and commodity markets is strongly influenced by company-specific, macroeconomic, or political news. Moreover, the existing literature (e.g., Chan, Bowman, & Neely, 2017;Chatrath, Miao, Ramchander, & Villupuram, 2014;Clements & Liao, 2017;Lahaye et al, 2011;Piccotti, 2018) has found that cojump occurrences are always related to macroeconomic news. Thus cojumps can be seen as an indicator, which may help forecast volatility.…”
Section: Introductionmentioning
confidence: 99%